Sports Orthopedics - Nehrer S; 2; Neubauer M; 2; Stotter C; 3 (Dynamic Media Sales Verlag, 2019)
Osteoarthritis degeneration of joints is a common process and increases in the older generation. 70-80% of people older than 70 are confronted with this condition, but fortunately only about 10-30 % have symptoms and pain. The triangle of age degeneration and inflammation is substantial to its etiology. Sports are popular amongst all generations and are accompanied by varying joint loads. Moreover, the number of people involved in recreational sport is increasing in western countries, some of which are high-impact sports such as tennis or soccer. Therefore osteoarthritis and sports is a challenging problem for sports physicians. The questionof the interaction of the degenerative process and the loading condition of various sports activities deals with the progression and /or onset of osteoarthritis through sports and recommendation of adequate sports modalities for osteoarthritic patients. Elite sports often lead to joint overload, but moderate training can induce adaption of the musculoskeletal system including improved cartilage conditions. Lately, sports programsare introduced to treat osteoarthritis by training of muscle-strength and coordination; this put sports and osteoarthritis in a new perspective of sports-medical care. Nevertheless, consulting sports physicians before the onset of complaints remains important in order to asses risk factors such as axis deformities, but also to adjust risk factors accordingly after the onset of symptoms. Therefore, prevention remains a central issue for sports physicians. KEY WORDS: Sports, Osteoarthritis, Cartilage, Training, Sports Overuse, Sports Injury